Response of biathletes organism to load in four consecutive annual training cycles - Paugschova, B.; Matiasko, M.; Murinova, A. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2013)
Aim of this paper was to show correlation between analysis of changes in selected spiroergometric parameters levels in four consecutive training cycles, and reached skiing preformance in World Cup biathlon sprint contest. Key parameters were maximum oxygen uptake (VO2max), maximum heart rate at AT (heart rate max) during preparation periods in training cycles and their relation to ski performance at World Cup Biathlon Sprint contest. M.K.`s difference of lowest heart rate percentage at AT from maximum HR recorded by us and highest heart rate percentage at AT from maximum HR is as much as 5,79%. It came to incease in AT ratio from maximum heart rate from 89,9% to 95,68%. M.M.`s difference (Table 3) between lowest heart rate percentage at AT from maximum HR and highest heart rate percentage at AT from maximum HR is 5,4%. It came to incease in AT ratio from maximum heart rate from 90,16% to 95,56%. On the basis of data shown we state, that heart rate percentage at AT from maximum HR correlated with changes in VO2max values (Figure 3, 4). Better ski performance achieved M.K., what is apparent also from spiroergometric examination, in which his VO2max maximum values are on very good level (Table 3). Although M.M.´s values in observed parameters improved annualy, his distance to top biathletes was always greater than in case of M.K. His VO2max values are lower compared to M.K., and steadiness of his performance fluctuates, as shown in laboratory exams. This unsteadiness was visible at World Cup too, where in Pokljuka he was able to ski on same level with the best and place 6th in total score. A week after, his ski-time was one minute slower and he placed significantly worse.